Characterization of 2D precision and accuracy for combined visual-haptic localization - Fischer, Madeline; Saetti, Umberto; Godfroy-Cooper, Martine; Fischer, Douglas (Frontiers in Neuroscience, 2025)
This article describes a combined visual and haptic localization experiment that addresses the area of multimodal cueing. The aim of the present investigation was to characterize two-dimensional (2D) localization precision and accuracy of visual, haptic, and combined visual-tactile targets in the peri-personal space, the space around the body in which sensory information is perceived as ecologically relevant. Participants were presented with visual, haptic, or bimodal cues using the body-centered reference frame and were instructed to indicate the corresponding perceived target location in space using a mouse pointer in an open-loop feedback condition. Outcomes of the unimodal (visual and haptic) and bimodal (combined visual-haptic) localization performance were used to assess the nature of the multisensory combination, using a Bayesian integration model. Results of the study revealed that the visual and haptic perceptive fields are characterized differently in terms of localization performance, providing important considerations for the transformation of each sensory modality when combining cues into a unified percept. The results reaffirmed many well known radial characteristics of vision with respect to localization, and identified a nonlinear pattern of haptic localization performance that was largely influenced by the midline of the center of the torso and each side of the cutaneous region. Overall, the lack of improvement in precision for bimodal cueing relative to the best unimodal cueing modality, vision, is in favor of sensory combination rather than optimal integration predicted by the Maximum Likelihood Estimation (MLE) model. Conversely, the hypothesis that accuracy in localizing the bimodal visual-haptic targets would represent a compromise between visual and haptic performance in favor of the most precise modality was rejected. Instead, the bimodal accuracy was found to be equivalent to or to exceed that of the best unimodal condition, vision. The results provide some insight into the structure of the underlying sensorimotor processes employed by the brain and confirm the usefulness of capitalizing on naturally occurring differences between vision and haptic to better understand their interaction and their contribution to multimodal perception These results will help inform the development of future human-machine interfaces implementing haptic feedback mechanisms In the context of pilot performance, haptic localization can have several benefits including enhanced situational awareness, improved spatial orientation, reduced workload, thereby contributing to safer operations. These benefits can be applied to future systems for aircraft handling by helping overcome visual illusions and discrepancies between visual and vestibular sensory channels, especially in degraded visual environments.